A novel adaptive control scheme for dynamic voltage restorer - Kiran, Tummala Kranti; Rajagopal, Balakrishnan; Raju, Yerramilli Butchi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
This study introduces a novel approach to improve the performance of the dynamic voltage restorer (DVR) using a control structure based on the inverse hyperbolic sine function-based least mean square (IHSF-LMS). The proposed control structure efficiently extracts the fundamental source voltage component with rapid convergence. The primary objective of this control scheme is to enhance compensation capability and maintain load voltage stability. Key features include superior steady-state performance and heightened robustness with reduced computational complexity. This approach achieves a reduction in peak overshoot and settling time compared to the traditional LMS method. The validation of system performance is conducted through MATLAB/Simulink simulations, demonstrating compliance with the IEEE-519-2014 standards for harmonic spectra.